Unilateral biportal endoscopy-induced intracranial pneumocephalus as radiographic evidence of raised intracranial pressure resulting from dural tear: a case report - Xie, Bin; Feng, Xiaoteng; Huang, Zhenghao; Cheng, Zhaojun; Long, Xiangyu; Huang, Chenxing; Zhong, Fangling; Yu, Weibo; Shen, GengYang; Liu, Shengyao; Zhao, Yu; Ren, Hui; et al. (Frontiers in Surgery, 2025)
Unilateral Bioportal Endoscopy (UBE), as a minimally invasive technique, has shown significant advantages in the treatment of spinal disorders. However, it comes with surgical risks and complications, particularly acute neurological deficits. In this report, we present a rare case of pneumocephalus as a complication following unilateral dual-channel spinal surgery (UBE) for lumbar disc herniation. A 54-year-old male patient underwent UBE-assisted disc removal surgery for L5-S1 disc herniation. No obvious dural tear was noted during the surgery. Postoperatively, the patient experienced difficulty awakening from anesthesia, with signs of altered consciousness. CT imaging revealed pneumocephalus. On the second postoperative day, cerebrospinal fluid leakage and symptoms of decreased intracranial pressure were observed. After symptomatic treatment, no significant neurological sequelae were noted, and the patient was discharged. Postoperative clinical signs of increased intracranial pressure and imaging evidence of pneumocephalus suggest the occurrence of dural injury.